Academic general practice in the UK medical schools, 1948-2000 : a short history - Howie, J. G. R. (John Garvie Robertson); Whitfield, Michael (Edinburgh University Press, 2011)
The first collective record of the evolution of general medical practice as an academic discipline over half a century This anthology captures the stories of the early struggles to set up university departments between visionary supporters and traditionalist blockers as well as the steadily increasing successes aided by a dedicated funding system. The accounts are written where possible by the people involved in the early developments of their subject. These tales are of vision, commitment and resilience and are interesting both in their own right and for the more general lessons they tell us about the processes of creating institutional change within a modern democracy. Key Features Demonstrates the radical shifts in the shape of medical education in the last two decades Provides vivid personal accounts from early academic leaders Includes comment on contemporary medical and educational developments